2020
DOI: 10.1590/1678-9865202033e190220
|View full text |Cite
|
Sign up to set email alerts
|

Influence of food consumption in the glycemic profile of children and adolescents with type 1 diabetes Mellitus

Abstract: Objective To review the dietary intake of children and adolescents with type 1 diabetes Mellitus and its association with the glycemic profile. Methods Longitudinal observational study. Dietary intake was measured using a three-day dietary record and the glycemic profile with a continuous glucose monitoring (range between 70 and 180mg/dL) and serum glycated hemoglobin levels (ideal <7.5%). Anthropometric data, insulin therapy, and carbohydrate counting were collected. Results The sample included 34 indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(29 reference statements)
0
3
0
1
Order By: Relevance
“…Şahin Bodur et al [25] found a trend of increased HbA1c in male patients with DM1 in a study with 110 adolescents, where 5% of the total sample (84 individuals) needed improvements in diet quality. Fritz et al [35] observed higher consumption of carbohydrates and fats and lower consumption of fiber in patients with DM1 and higher HbA1c levels in 34 children and adolescents with DM1 in a Brazilian study. However, unlike the present study, previous studies found no statistically significant association between increased consumption of ultra-processed foods/quality of diet and higher HbA1c levels [8,35,36].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Şahin Bodur et al [25] found a trend of increased HbA1c in male patients with DM1 in a study with 110 adolescents, where 5% of the total sample (84 individuals) needed improvements in diet quality. Fritz et al [35] observed higher consumption of carbohydrates and fats and lower consumption of fiber in patients with DM1 and higher HbA1c levels in 34 children and adolescents with DM1 in a Brazilian study. However, unlike the present study, previous studies found no statistically significant association between increased consumption of ultra-processed foods/quality of diet and higher HbA1c levels [8,35,36].…”
Section: Discussionmentioning
confidence: 89%
“…Fritz et al [35] observed higher consumption of carbohydrates and fats and lower consumption of fiber in patients with DM1 and higher HbA1c levels in 34 children and adolescents with DM1 in a Brazilian study. However, unlike the present study, previous studies found no statistically significant association between increased consumption of ultra-processed foods/quality of diet and higher HbA1c levels [8,35,36]. However, Rocha et al [11] identified excessive consumption of these foods in the population with DM1, and the determining factors for the choice were lower family income and lower educational level of those responsible.…”
Section: Discussionmentioning
confidence: 89%
“…Fritz et al 50 conducted a study with children and adolescents aged 9 to 17 years and observed that children with MS presented inadequate diet, consumed a lot of calories and were inactive compared to those without MS. The ndings of Paula, Luz and Ferreira 51 suggest that reducing the consumption of high-calorie, nutrient-poor foods and increasing the intake of ber, fruits and vegetables are important habits for the prevention of MS.…”
Section: Discussionmentioning
confidence: 99%
“…A contagem de carboidratos atua como um facilitador na manutenção da glicemia estável por um maior tempo, apesar do consumo alimentar inadequado dos adolescentes (19) .…”
Section: Osunclassified